1994
DOI: 10.1088/0967-3334/15/2/009
|View full text |Cite
|
Sign up to set email alerts
|

Design of an inductive plethysmograph for ventilation measurement

Abstract: We have designed an inductive plethysmograph to obtain a non-invasive measure of ventilation. Two elastic bands containing insulated wires encircle the chest and abdomen--the inductance of each band depends on the enclosed cross sectional area. Each inductive band forms an element in a tank circuit, which determines the resonant frequency of a Colpitts oscillatory. By measuring the oscillatory frequency, we indirectly measure the changes in cross sectional area that occur during breathing. Independent measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 3 publications
(2 reference statements)
0
15
0
Order By: Relevance
“…Specifically, the selfinductance of the bands and thus the frequency output from connected oscillator-demodulator k changed monotonically with inspiration and expiration, as in a volume signal. 15,16 The signals were digitized for display and analysis. The voltage spans of the V rib or V abd were equalized by stretching these bands with 2 parallel rods, and the gain settings were unchanged throughout the study.…”
Section: Respiratory Inductance Plethysmographymentioning
confidence: 99%
“…Specifically, the selfinductance of the bands and thus the frequency output from connected oscillator-demodulator k changed monotonically with inspiration and expiration, as in a volume signal. 15,16 The signals were digitized for display and analysis. The voltage spans of the V rib or V abd were equalized by stretching these bands with 2 parallel rods, and the gain settings were unchanged throughout the study.…”
Section: Respiratory Inductance Plethysmographymentioning
confidence: 99%
“…Cohen et al [16] evaluated an RIP in relation to an impedance plethysmograph and a spirometer. They demonstrated that tapping the RIP produced smaller artefacts than touching the impedance electrodes; though both these devices registered artefacts from arm movements, the spirometer was immune.…”
Section: Discussionmentioning
confidence: 99%
“…A design for an RIP has been given by Cohen et al [16]. The subject has to wear zig zag loops of wire (10 cm or so in depth, therefore quite restrictive) sewn onto an elasticized body band, available in infant, child, and adult sizes.…”
Section: Respiratory Inductance Plethysmography (Rip)mentioning
confidence: 99%
“…Direct monitoring is preferred over the use of respiratory or apnea monitors, which may sense false flow impedance changes that are more indicative of abdominal manipulation during surgery (false diaphragmatic motions) than effective respiration. 103 Similarly, monitoring of respiration solely on the basis of rebreathing bag movement may result in an inaccurate assessment.…”
Section: Monitoringmentioning
confidence: 99%